Effect of Antiplatelet and Anticoagulant Therapy on Postoperative Hemostasis and Tissue Healing - Faisal Toheed, Fida Hussain, Saima Bukhari, Rana Shoaib Aslam, Abrar Ul Hassan Pirzada, Asadullah Awan (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Antiplatelet and anticoagulant drugs are extensively used as prevention against cardiovascular and thromboembolic diseases. There is a clinical dilemma in their perioperative management because it is associated with high risks of bleeding and possible wound healing impairments. Objective: To evaluate the effect of antiplatelet and anticoagulant therapy on postoperative hemostasis and tissue healing in patients undergoing surgical procedures. Methodology: This was a prospective observational study that involved 67 patients that underwent antithrombotic treatment and post-operative surgery between January and June 2023 at Allam Iqbal Teaching Hospital, D.G. Khan. Patients have been subdivided into three groups: the antiplatelet therapy, anticoagulant therapy and the combination therapy. Coagulation profile before the operation, blood loss during operation, blood loss after operation, wound healing condition, and postoperative complication were documented. ANOVA and Chi-square were used to conduct the statistical analysis, with p [?] 0.05 taken as significant. Results: Patients receiving combined therapy showed significantly higher PT, APTT, and INR values (p < 0.001). Postoperative bleeding was more frequent in the combined therapy group (55%) compared to anticoagulant (36.4%) and antiplatelet groups (20%) (p = 0.01). Delayed wound healing and longer hospital stay were also significantly associated with combined therapy (p = 0.04 and p = 0.01 respectively). Major bleeding requiring re-operation or transfusion remained uncommon. Conclusion: Antithrombotic therapy, particularly combined antiplatelet and anticoagulant use, increases postoperative bleeding risk and delays wound healing but rarely leads to severe complications. Careful perioperative management allows safe continuation of therapy in most patients. Keywords: Antiplatelet, Anticoagulant, Postoperative bleeding, Hemostasis, Wound healing, Surgery.